Carbonaceous aerosol characteristics on the Third Pole: A primary study based on the Atmospheric Pollution and Cryospheric Change (APCC) network. (October 2019) - Chen, Pengfei; Kang, Shichang; Li, Chaoliu; Zhang, Qianggong; Guo, Junming; Tripathee, Lekhendra; Zhang, Yulan; Li, Gang; Gul, Chaman; Cong, Zhiyuan; Wan, Xin; Niu, Hewen; et al.
Abstract: Carbonaceous aerosols (CAs) scatter and absorb incident solar radiation in the atmosphere, thereby influencing the regional climate and hydrological cycle, particularly in the Third Pole (TP). Here, we present the characteristics of CAs at 19 observation stations from the Atmospheric Pollution and Cryospheric Change network to obtain a deep understanding of pollutant status in the TP. The organic carbon (OC) and elemental carbon (EC) concentrations decreased noticeably inwards from outside to inland of the TP, consistent with their emission load and also affected by transport process and meteorological condition. Urban areas, such as Kathmandu, Karachi, and Mardan, exhibited extremely high OC and EC concentrations, with low and high values occurring in the monsoon and non-monsoon seasons, respectively. However, remote regions inland the TP (e.g., Nam Co and Ngari) demonstrated much lower OC and EC concentrations. Different seasonal variations were observed between the southern and northern parts of the TP, suggesting differences in the patterns of pollutant sources and in distance from the sources between the two regions. In addition to the influence of long-range transported pollutants from the Indo-Gangetic Plain (IGP), the TP was affected by local emissions (e.g., biomass burning). The OC/EC ratio also suggested that biomass burning was prevalent in the center TP, whereas the marginal sites (e.g., Jomsom, Dhunche, and Laohugou) were affected by fossil fuel combustion from the up-wind regions. The mass absorption cross-section of EC (MACEC ) at 632 nm ranged from 6.56 to 14.7 m 2  g −1, with an increasing trend from outside to inland of the TP. Urban areas had low MACEC values because such regions were mainly affected by local fresh emissions. In addition, large amount of brown carbon can decrease the MACEC values in cities of South Asia. Remote sites had high MACEC values because of the coating enhancement of aerosols. Influenced by emission, transport process, and weather condition, the CA concentrations and MACEC presented decreasing and increasing trends, respectively, from outside to inland of the TP. Graphical abstract: Image 1 Highlights: CA concentrations decrease remarkably inwards from outside to inland of the TP. CA seasonal variation suggest a different source pattern between south and north parts of TP. The TP is affected by local biomass burning in addition to long-range transport pollutants. MACEC increase from outside to inland of the TP because of aging and coating processes.